2021
DOI: 10.1111/irv.12916
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of SARS‐CoV‐2 infection and SARS‐CoV‐2 positive hospital admissions among children in South Africa

Abstract: Introduction: We describe epidemiology and outcomes of confirmed SARS-CoV-2 infection and positive admissions among children <18 years in South Africa, an upper-middle income setting with high inequality. Methods: Laboratory and hospital COVID-19 surveillance data, 28 January -19 September 2020 was used. Testing rates were calculated as number of tested for SARS-CoV-2 divided by population at risk; test positivity rates were calculated as positive tests divided by total number of tests. In-hospital case fatali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
1
15
1
Order By: Relevance
“…Our findings regarding the relative frequency and severity of COVID-19 in children are consistent with those in the literature, specifically that pediatric SARS-CoV-2 infections are common but largely mild or subclinical . Another study in Nicaragua reported that 37.7% of children younger than 15 years were seropositive for SARS-CoV-2, which is substantially lower than the 49.8% (95% CI, 47.5%-52.1%) we observed in our study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings regarding the relative frequency and severity of COVID-19 in children are consistent with those in the literature, specifically that pediatric SARS-CoV-2 infections are common but largely mild or subclinical . Another study in Nicaragua reported that 37.7% of children younger than 15 years were seropositive for SARS-CoV-2, which is substantially lower than the 49.8% (95% CI, 47.5%-52.1%) we observed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…27 Our findings regarding the relative frequency and severity of COVID-19 in children are consistent with those in the literature, specifically that pediatric SARS-CoV-2 infections are common but largely mild or subclinical. [5][6][7] Another study 32 in Nicaragua reported that 37.7% of children younger than 15 years were seropositive for SARS-CoV-2, which is substantially lower than the 49.8% (95% CI, 47.5%-52.1%) we observed in our study. This rate was, however, consistent with that estimated from a previously published analysis 27 in a household transmission cohort in the same community where 56.7% of participants were infected.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In SA, on September 2020, the total laboratory-confirmed COVID-19 cases in South African children were 228 per 100,000 and were lower than the 829 per 100,000 children in the United States. COVID-19 cases in children in SA were higher compared to rates of less than 100 per 100,000 children in Norway and Australia [10]. UNICEF report from 96 countries in 2020 has indicated that children and adolescents less than 20 years have accounted for 21% of the COVID-19 cases and 33% of the 2020 population [27].…”
Section: Covid-19 Distribution In Sa Children and Children From Other...mentioning
confidence: 99%
“…There are few studies conducted on the epidemiology and clinical manifestation of COVID-19 in African children in comparison to continents such as China, Europe, and North America [10,21,29]. The findings of studies from other countries cannot be generalizable to South African children because of the differences in the risk factors predisposing children to COVID-19, mostly the burden of infectious diseases [10].…”
Section: Risk Factors Predisposing South African Children To Covid-19...mentioning
confidence: 99%